2013
DOI: 10.1080/13607863.2013.837150
|View full text |Cite
|
Sign up to set email alerts
|

Dementia in the movies: the clinical picture

Abstract: The clinical picture of dementia portrayed in fictional movies is mild and may be misleading.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
25
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 27 publications
(26 citation statements)
references
References 19 publications
0
25
0
1
Order By: Relevance
“…In the novel Iris [25], this was shown as forgetting to come out with the right words: "She suddenly finds it difficult in front of a large audience to come out with the words to reply to questions, something with which she has previously been quite at ease" ( [25], p. 441). Gerritsen et al [49] analysis of 23 fictional movies with a theme of dementia reports that 18 films showed memory problems, and 10 showed word finding difficulties.…”
Section: Depiction Of People With Dementiamentioning
confidence: 99%
“…In the novel Iris [25], this was shown as forgetting to come out with the right words: "She suddenly finds it difficult in front of a large audience to come out with the words to reply to questions, something with which she has previously been quite at ease" ( [25], p. 441). Gerritsen et al [49] analysis of 23 fictional movies with a theme of dementia reports that 18 films showed memory problems, and 10 showed word finding difficulties.…”
Section: Depiction Of People With Dementiamentioning
confidence: 99%
“…In the context of cinema films, the explicit portrayal of the clinical picture of dementia has been found to be fairly accurate but with an emphasis on cognitive symptoms, fluctuations of consciousness and disengaged behaviour (Gerritsen, Kuin, & Nijboer, 2014) and a failure to portray people with dementia as active agents. Drawing on Post's (1995) description of hyper-cognitivism, Swinnen (2012) reflects on the possibility that films contribute towards maintaining the stigma of dementia and to people's perception of a dissolution of the self through their emphasis on cognitive difficulties (such as language and memory).…”
Section: Portrayal In the Mediamentioning
confidence: 99%
“…Capstick 2007 for a full discussion), some commentators suggested that the performance of the actor in the central role was not entirely convincing as a person with dementia. In keeping with the findings of Gerritsen (2014), in this case, the urge to avoid caricature or undue negativity resulted in a portrayal which for the most part resembled, as one viewer noted, "mild depression, rather than dementia." As Miles and Plate (2004) note in their critique of capitalist/industrialist cinema, films made in these alternative traditions are more likely to encourage identification with the other as a fellow human being than as an alien or victim of disease.…”
Section: Towards Epistemic Justicementioning
confidence: 75%